Soft Tissue Augmentation Techniques and Materials Used in the Oral Cavity: An Overview. Issue 3 (June 2016) - Wolff, Jan; Farré-Guasch, Elisabet; Sándor, George K.; Gibbs, Susan; Jager, Derk Jan; Forouzanfar, Tymour
Abstract : Purpose: Oral soft tissue augmentation or grafting procedures are often necessary to achieve proper wound closure after deficits resulting from tumor excision, clefts, trauma, dental implants, and tooth recessions. Materials and Methods: Autologous soft tissue grafts still remain the gold standard to acquire a functionally adequate zone of keratinized attached gingiva. However, soft tissue substitutes are more commonly used because they minimize morbidity and shorten surgical time. Results: This review aimed to assess soft tissue grafting techniques and materials used in the oral cavity from existing literature. There are a large variety of materials and techniques, including grafts, local flaps, allogenic derived matrices such as acellular dermal allograft, xenogenic tissue matrices from animal origin, and synthetic materials. Conclusions: Tissue engineering of oral mucosa represents an interesting alternative to obtain sufficient autologous tissue for reconstructing oral wounds using biodegradable scaffolds, and may improve vascularization and epithelialization, which are critical for successful outcomes.